درجة تمثيل كتب اللغة العربية للمرحلة الأساسية العليا لمنحى الإقتصاد المعرفي - الحايك، آمنة خالد (جامعة آل البيت - عمادة البحث العلمي, 2015)
هدفت هذه الدراسة إلى التعرف إلى درجة تضمين منحى الاقتصاد المعرفي في مناهج اللغة العربية للمرحلة الأساسية العليا، لذا قامت الباحثة بباء قائمة بمجالات الاقتصاد المعرفي، تضمنت خمسة مجالات رئيسة، اندرج تحتها (50) ملمحا من ملامح الاقتصاد المعرفي التي اتفق عليها المحكمون. تكونت عينة الدراسة من كتب مهارات الاتصال للمرحلة الأساسية العليا جميعها، واستخدمت الباحثة لتحقيق هدف الدراسة المنهج الوصفي التحليلي، وتوصلت الدراسة إلى أن المجال الوطني قد حظي بالمرتبة الأولى، يليه المجال التكنولوجي، إذ وردا بدرجة مقبولة ومنطقية، أما المجال الاقتصادي، والمجال المعرفي فقد تضمنتهما المناهج بدرجة متدنية. ويمكن تفسير قصور مناهج مهارات الاتصال للمرحلة الأساسية العليا في تغطية مهارات هذين المجالين بتركيز مؤلفيها على المضامين اللغوية والعقلية، على اعتبار أن هذه المهارات هي التي تعمل على إكساب الطلبة القدرة اللغوية، وتنمي لديهم المهارات الذهنية. وأوصت الباحثة بإعادة النظر في بناء مناهج مهارات الاتصال للمرحلة الأساسية العليا، وبخاصة ما يتعلق بالمجالين الاقتصادي، والمعرفي اللذين وردا في المناهج بنسب مئوية متدنية.
This study aims at identifying the degree to which we include knowledge- based economy in the Arabic Language curricula for the higher elementary stage. In order to do so, the researcher made a list of the knowledge-based economy fields. Within these fields, there were fifty aspects of the knowledge-based economy on which the referees have agreed. The sample of the study consists of all the communication skills' books for the higher elementary stage. To achieve the goal of this study، the researcher has used the analytical descriptive course. The study has showed that the national field has come in the first rank، followed by the technological field with acceptable and rational percentages. As for the economic and based-knowledge fields، they have been included in the curricula with low percentage. The shortage of the curricula of the higher elementary communication skills in covering the latter two fields can be referred to the reason that the authors of the books have focused on the linguistic and mental concepts because they thought that those skills are the ones which enable the students develop the linguistic and mental skills. The researcher has pointed out one main recommendation that it is important to review the curricula of the communication skills for the higher elementary stage; specially the ones of the economic and based-knowledge fields.
Keywords: المدارس الأساسية -- المناهج الدراسية -- كتب اللغة العربية -- المحتوى الدراسي -- الإقتصاد المعرفي